PENGARUH MODEL ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION) TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS XI SMA SWASTA NASIONAL PETATAL - Rafika Muspita Sari; Susi Masniari Nasution; Karimaliana Karimaliana; Intan Permata Sari (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research aims to determine the effect of the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) model on the ability to write explanatory texts in class XI students at Petatal National Private High School." The sample in this study consisted of 65 students. This research method is an experimental method and the research design is post-test only control group design. The data collection instrument uses a test in the form of a Student Worksheet (LKS) to write explanatory text with the criteria: text structure, text integration, text characteristics, and accuracy of writing Enhanced Spelling (EyD). The results of data analysis obtained from the post-test scores for the ability to write explanatory text without using the ARIAS model (Assurance, Relevance, Interest, Assessment, Satisfaction) obtained the highest score of 80, the lowest score of 65, the average was 72.58. Meanwhile, the post-test score using the ARIAS model (Assurance, Relevance, Interest, Assessment, Satisfaction) obtained the highest score of 90, the lowest score was 75, the average was 84.41. From the calculation of the "t" test, the "t" table is then consulted at the 5% or 1% significance level with dk = (NI + N2) - 2 = 63. In the "t" table the level with dk = 63 is at a significance level of 5% = 2 .00, and 1% significance level = 2.65. It turns out that the to obtained is greater than ttable, namely 73.93 > 2.00 and 73.93 > 2.65.Â Keywords: ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction), Writing,Â Explanatory Text Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) terhadap kemampuan menulis teks eksplanasi pada siswa kelas XI SMA Swasta Nasional Petatalâ€. Sampel pada penelitian ini berjumlah 65 siswa. Metode penelitian ini adalah metode eksperimen dan desain penelitian adalah Post-test only control group design. Instrumen pengumpulan data menggunakan Tes yang berbentuk Lembar Kerja Siswa (LKS) untuk menulis teks eksplanasi dengan kriteria: struktur teks, keterpaduan teks, ciri-ciri teks, dan ketepatan penulisan Ejaan yang Disempurnakan (EyD). Hasil analisis data yang diperoleh dari nilai Post-test kemampuan menulis teks eksplanasi tanpa menggunakan model ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) memperoleh nilai tertinggi 80, nilai terendah 65, rata-rata 72,58. Sedangkan nilai Post-test dengan menggunakan model ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) memperoleh nilai tertinggi 90, nilai terendah 75, rata-rata 84,41. Dari perhitungan uji â€œtâ€ selanjutnya dikonsultasikan dengan tabel â€œtâ€ pada taraf signifikan 5% maupun 1% dengan dk= (NI + N2) â€“ 2 = 63. Pada tabel â€œtâ€ taraf dengan dk = 63 taraf signifikan 5% = 2,00, dan taraf signifikan 1% = 2,65.Â Kata kunci: ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction), Menulis, Teks Eksplanasi